Do Fundamental and Behavioral Factors Affect Insurance Company’s Stock Returns? - Rachman, Ari Nur; Wijayanto, Andhi (Universitas Negeri Semarang, 2021)
This study aims to determine the effect of fundamental factors and behavioral finance on stock returns. The company's financial performance variables use Return on equity (ROE) and Earnings per Share (EPS) as proxies. The macroeconomic condition variable uses the exchange rate and the BI rate as a proxy. Investor sentiment variable uses Trading Volume Activity (TVA) and Consumer Confidence Index (CCI) as proxies. The object of this research is the insurance sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The research sample was selected using purposive sampling method so that 12 companies were selected as samples. The data analysis method used was multiple regression using the Eviews 9 tool. The results showed that the company's financial performance variables and macroeconomic conditions had no effect on stock returns. Investor sentiment with TVA proxy has a significant positive effect on company returns, while CCI has no effect on company returns.